2021
DOI: 10.3390/jmse9121381
|View full text |Cite
|
Sign up to set email alerts
|

Depth Profiles of Microplastics in Sediment Cores from Two Mangrove Forests in Northern Vietnam

Abstract: Plastics are essential materials that play critical roles in people’s lives in the modern world. However, plastic pollution in the ocean has become a critical environmental problem due to the fact of its durability and long life span. In the present study, we analyze the contamination of microplastics in sediment cores from mangrove forests of the Red River Delta and Tien Yen Bay in Northern Vietnam. The results showed that the concentration of microplastics in sediment cores ranged from 0 to 4941 particles/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 44 publications
2
2
0
Order By: Relevance
“…The present study did not detect other common resins such as polyvinyl chloride (PVC), acrylic, and polyurethane (PU) in all sediment cores. The polymer composition of microplastics in Lach Huyen sediment has similarities with the previous report in the Red River estuary and Tien Yen bay, Vietnam [25].…”
Section: D) Chemical Composition Of Microplasticssupporting
confidence: 85%
“…The present study did not detect other common resins such as polyvinyl chloride (PVC), acrylic, and polyurethane (PU) in all sediment cores. The polymer composition of microplastics in Lach Huyen sediment has similarities with the previous report in the Red River estuary and Tien Yen bay, Vietnam [25].…”
Section: D) Chemical Composition Of Microplasticssupporting
confidence: 85%
“…The microplastics found in this study were mostly in fiber form, as in previous studies in mangrove core sediments in southern Thailand, Hangzhou Bay, China, and Northern Vietnam (Jingjing Luu Viet et al, 2021;. Moreover, many previous studies also suggested that the fiber type is detected as a major shape of microplastics in mangrove environments (biota: (Hastuti et al, 2019;Klangnurak & Chunniyom, 2020), sediments: (Mohamed Nor & Obbard, 2014;Wang et al, 2020;Zuo et al, 2020)).…”
Section: Countrysupporting
confidence: 84%
“…M icroplastics are om nipresent in our environm ent for long tim e. Many researchers found the evidence of historical changes in microplastic deposition. Sediment cores are providing insight long-term microplastic record in ocean (Matsuguma et al, 2017;Uddin et al, 2021), lacustrine (Dong et al, 2020;Turner et al, 2019), coastal (Asadi et al, 2019), estuary (Willis et al, 2017), and mangrove (Luu Viet et al, 2021). Especially, Mangrove forest have an potential for trap marine litter (Martin et al, 2019).…”
Section: List Of Tablesmentioning
confidence: 99%
“…We compared the HML sedimentary microplastic abundance with results in the 22 sediment records after 1980 globally (Figure and Table S8). The HML microplastic abundance was 200.9 ± 147.5 items g –1 after 1980, which was much higher than the abundances in Xiamen Bay (71.5 ± 64.6 items g –1 ), Wuliangsuhai Lake (5.0 ± 2.1 items g –1 ), and other regions in China. ,,, The abundance in HML was also significantly higher than the levels in Lake Saimaa, Finland (4.4 ± 1.1 items g –1 ), Jinhae Bay, South Korea (2.6 ± 2.4 items g –1 ), and other global sediments. , One of the reasons could be the geographical characteristics of the sampling area and the hydrodynamic influences in water bodies. , The microplastic particles can be swiftly transported by ocean currents and tides, impeding effective sediment settlement . However, HML is isolated from any external water body, and the lower hydrodynamic condition facilitates stable and rapid microplastic accumulation.…”
Section: Discussionmentioning
confidence: 82%